THE CONTRIBUTION OF THE IFG IN MUNICIPAL CULTURAL PLANNING OF ANÁPOLIS-GO: THE USE OF RESEARCH DATA FOR BASEMENT OF PUBLIC POLITICAL - Boaventura, Dáguila da Silva; Godinho Miranda, Elza Gabriela (Cadernos de Educação Tecnologia e Sociedade, 2016)
This article describes the steps of the research that accompanied the participation of the IFG in the preparation of the Municipal Culture Plan (PMC) of Anápolis-GO/Brazil, as one of consolidating elements of its Municipal Culture System (SMC). The Municipal Secretary of Culture (SEMUC) and the Municipal Culture Council (CMC), in maintaining a direct contact with the Federal Institute of Goiás - Campus Anápolis and in recognition of activities and research carried out by the institution since 2010 in the promotion and enhancement of local culture, invited the IFG to participate in the construction of the PMC, especially in the first stage of diagnosis of the local culture. This is the first step in the preparation of the plan, establishing objectives, goals, investments, for each cultural sector within ten (10) years. The SMC is the means of participation of municipalities in the National Culture System (SNC), which aims to integrate the information and planning of the national culture as the example of other existing systems, like Health Unic System (SUS). Its operation is described in the National Culture Plan (PNC), the culture of planning in the country that combines state and municipal plans. It was established by Law 12.343/2010 which defined principles, objectives, the role of government, forms of financing and evaluation given its implementation. Provides integration of different spheres (Federal, State, Federal District and municipalities), through voluntary accession of entities, which are obliged to draw up their own culture plan. After accession, Anápolis prepared its PMC, implemented in 2013 as a law. The process was accompanied and documented by IFG, who collaborated in the preparation of the PMC text in the CMC meetings in forums and Culture Conference, sector meetings, and presented as a result of research the necessary information requested by SEMUC, and follows as a participant and evaluator results.